ASSESSMENT OF CENTRAL HEMODYNAMICS IN DIABETES WITH ENDOTOXEMIA - Salimova M.M; Uzakov D.K; Mirubaydov N.Sh.; Ibragimov N.N. (Bright Mind Publishing, 2026)
Diabetes mellitus is currently one of the fastest-growing chronic diseases worldwide, continuing to spread at an alarming rate across all regions. According to data from the International Diabetes Federation (IDF), an estimated 537 million people were living with diabetes in 2021, and this number is projected to rise to 783 million by 2045 [1]. The late complications of diabetes, particularly purulent–septic inflammations of the lower limbs — such as diabetic foot syndrome, phlegmon, and gangrene — have a profoundly negative impact on patients’ quality of life. These conditions are associated with a markedly increased risk of limb amputation and mortality.
Keywords: Diabetes mellitus; sepsis; endotoxicosis; central hemodynamics; NT-proBNP; lactate; echocardiography; microcirculation; vasoplegia; cardiogenic dysfunction.